Hierarchical ordered macro/mesoporous titania with a highly interconnected porous structure for efficient photocatalysis. Issue 42 (6th October 2016) - Zhao, Tao; Ren, Yuan; Yang, Jianping; Wang, Lianjun; Jiang, Wan; Elzatahry, Ahmed A.; Alghamdi, Abdulaziz; Deng, Yonghui; Zhao, Dongyuan; Luo, Wei
Abstract : Hierarchical ordered macro/mesoporous titania with a highly interconnected porous structure was synthesized via a facile bi-template interface deposition method for efficient photocatalysis applications. Abstract : In this study, a 3-dimensional interconnected hierarchical ordered macro/mesoporous titania (HOPT) with thin walls, crystalline framework, large cavities (∼420 nm), uniform mesopores (3.7 nm) and high surface area (177 m 2 g −1 ) was synthesized through a facile bi-template interface-directed deposition method using poly(propylene oxide)- block -poly(ethylene oxide)- block -poly(propylene oxide) (Pluronic P123) triblock polymer as a soft template and structure directing agent, titanium isopropoxide (TIPO) as a titania source and 3-dimensional ordered macroporous carbon (3DOMC) as the hard template and the nanoreactor. This was followed with a two-step thermal treatment in nitrogen and air. Under simulated sunlight irradiation at room temperature, the HOPT shows an ultrahigh photocatalytic activity for the degradation of Rhodamine B (RhB) with a fast reaction rate that is three times higher than commercial titania nanoparticles (P25).